Correlação entre o método de análise quantitativa da deposição e uso do papel hidrossensível em aplicações aéreas - Santana, Thalyson Medeiros de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Evaluations of the spray deposits are used in research as a tool to develop and improve the techniques of plant protection product application. In this way, our aim was to correlate the syrup deposition in water sensitive paper with the deposition on glass slides in order to analyze the applications flights from pesticides. The experiment consisted of four applications being held in Recanto in the municipality of Sidrolândia-MS and one in Savannah Farm in municipality of Chapadão do Céu-GO. In the first three applications, the syrup was made by insecticide Curbix 200 SC and fourth application, the insecticide ENGEO Pleno. In both assays, quantification of deposits was taken with Brilliant Blue dye. The water sensitive paper was analyzed using the software DropScan® (Leon Systems), for the variables: coverage (%) drops density (drops cm-2), volume diameter (DV0,1; DV0,5 and DV0,9) and median diameter (NMD). The spray deposition data in the blades were subjected to Pearson correlation analysis with the results of the deposition variation coefficient coverage of drops, density and quantitative deposition estimated by calculating the volumes of the droplets based on the diameters provided by the software (DMN, DV0,1, and DV0,5 DV0,9), which were multiplied by the density of droplets in the water sensitive paper. Correlations between the parameters provided directly by DropScan (coverage and density of drops) and analysis of the deposition on the blades did not provide a set of robust data that provided security for the use of all water sensitive paper + software as an alternative form of assessment spraying, in direct comparison with the method of analysis of the deposition on the blades. In two of the applications evaluated, ...

As avaliações dos depositos da pulverizacão são utilizadas nas pesquisas como instrumento para desenvolver e melhorar as tecnicas de aplicacão dos produtos fitossanitarios. Nesse sentido, o objetivo desse trabalho foi correlacionar a deposição da calda no papel hidrossensível com a deposição em lâminas de vidro de modo a analisar as aplicações aéreas de produtos fitossanitários. O experimento foi composto por quatro aplicações sendo realizadas na Fazenda Recanto no município de Sidrolândia-MS e uma na Fazenda Savana, no município de Chapadão do Céu-GO. Nas três primeiras aplicacoes, a calda foi composta pelo inseticida Curbix 200 SC e na quarta aplicacão, pelo inseticida Engeo Pleno. Em ambos os ensaios, a quantificação dos depositos foi feita com o corante alimentício Azul Brilhante . Os papeis hidrossensíveis foram analisados através do software DropScan® (Leon Sistemas), para as variáveis: cobertura (%), densidade de gotas (gotas cm-2), diâmetro volumétrico (DV0,1; DV0,5 e DV0,9) e diâmetro mediano numérico (DMN). Os dados de deposição da calda nas lâminas foram submetidos à análise de correlação de Pearson com os resultados de coeficiente de variação da deposição, cobertura das gotas, densidade de gotas e deposição quantitativa estimada pelo cálculo dos volumes das gotas baseados nos diâmetros fornecidos pelo software (DMN, DV0,1, DV0,5 e DV0,9), os quais foram multiplicados pela densidade de gotas nos papéis hidrossensíveis. As ...
Correlation between quantitative method analysis of deposition and use of hydro-sensible paper in air applications
Keywords: Defensivos vegetais - Tecnologia de aplicação; Pulverização; Aeronautica na agricultura; Spraying